Pengaruh Kejelasan Sasaran Anggaran, Penerapan Sistem Akuntansi dan Kompetensi Aparatur terhadap Akuntabilitas Pengelolaan Keuangan Desa - Estrilia, Devi; Wijayanti, Iin; Hidayah, Nurul (Jurnal Manajemen, 2023)
This study aims to determine the effect of the clarity of budget targets, the application of the financial accounting system, and the competence of the village apparatus on the accountability of village financial management in Poncol District, Magetan Regency. This study uses a quantitative approach using primary data. The sample used in the study was 77 village officials. The method of data collection is in the form of a questionnaire with a Likert measurement scale. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The results of the research on the first hypothesis indicate that the clarity of budget targets has a positive and significant effect on village financial management accountability. The results of the research on the second hypothesis indicate that the application of the accounting system has a positive and significant effect on village financial management accountability. The results of the research on the third hypothesis indicate that the competence of the apparatus has a positive and significant effect on the accountability of village financial management. Simultaneously, the three independent variables affect the dependent variable, which is 61%.